Identification through sire catalogues analysis and molecular detection of brachyspina carriers in Uruguayan Holstein (FAVE Sección Ciencias Veterinarias, 2020)
Brachyspina syndrome is a hereditary recessive disease of recent identification in the Holstein breed. It is caused by a deletion of 3.3Kb in the FANCI gene located in the bovine chromosome 21. The mutation was identified in Holstein populations of Europe, North America and Asia. Given the economic importance of the defect and its wide distribution, the objective of this work was the identification of carrier animals in the genetic selection nucleus of the breed in Uruguay and the molecular verification of the deleterious allele in animals of the national herd. In the present study, 2598 records of Holstein bulls were analyzed from the list of parents of the dairy genetic evaluation system, records of bulls belonging to the Holstein semen catalogs available for Uruguay from 2014 to 2018; and 71 cows belonging to the general herd. Twenty-eight brachyspina carrier bulls were found of a total of 377 bulls with genetic information from the list of parents and four carrier cows of a total of 71 genotyped in our laboratory. A decrease in the income of semen from carrier animals to the country between 2014 and 2018 was demonstrated. The significant frequency of carrier animals in Uruguay evidences the need to implement strategies to gradually eliminate the population defect.
Keywords: Bos taurus; hereditary disease; artificial insemination; fertility